Analisis Kemampuan Membaca dan Menulis Siswa Kelas lll SDN 145 Kota Pekanbaru (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The purpose of this study is to identify the weaknesses faced by elementary school students during the learning process, particularly in reading and writing skills. Basic literacy problems remain a major challenge for some students, especially at the lower and middle grade levels. This study was conducted with third-grade students at SDN 145 Pekanbaru using a qualitative descriptive approach through observation and analysis of students’ literacy abilities. The results show that the reading and writing skills of third-grade students at SDN 145 Pekanbaru vary. Most students are able to read fluently; however, they still experience difficulties in writing, such as spelling errors, sentence structure issues, and poor handwriting neatness. On the other hand, there are also students who still have difficulty reading and often need to spell out words letter by letter. In addition, students’ interest in reading and writing activities is relatively low, which affects the suboptimal development of their literacy skills. This low level of interest is influenced by a lack of motivation, undeveloped reading habits, and minimal learning assistance. Therefore, efforts that teachers can undertake to improve students’ interest and abilities in reading and writing at SDN 145 Pekanbaru include organizing additional classes, providing intensive guidance, and applying a personal approach to motivate students and build their confidence in improving basic literacy skills.